Comparison of Regulatory Substantive Examination of Industrial Design in Food Packaging Drawings: An Indonesian and Japanese Study - Fauziyyah, Laila; Sakti, Muthia (UNIVERSITAS PAKUAN, 2025)
AbstractProtection of industrial designs for food packaging is vital to preserve originality and legal certainty. In Indonesia, substantive examination remains reactive triggered only by third-party objections during the publication period creating potential uncertainty, as seen in the red ginger drink packaging dispute between PT Aneka Boga Citra and PT Total Asri Sumber Alam. In contrast, Japan applies a full examination from the outset to assess novelty and originality. Using a normative juridical method (comparative approach and case studies), this study finds that full examination effectively strengthens protection and prevents disputes. This research recommends that Indonesia must adopt a Hybrid Substantive Examination Model combining rigorous expert review with AI technology. Keywords : Industrial Design, substantive examination, comparative law.